Meninjau Kembali Kebijakan dan Program Reunifikasi Anak Jalanan di Indonesia - Muhrisun Afandi (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2018)
For the umpteenth time various programs have been developed in response to the problems of street children in Indonesia. The government has officially attempted to address the problems through a number of avenues. However, the overall effort appears to be cursory at best. Only a small number of street children seem to benefit from the official programs, while the number of this population continues to climb.In spite of the failures of previous programs, the government seems to be reluctant to change its position and to undertake alternative approaches in addressing the problems of street children. Intervention programs for street children in Indonesia, in the provincial and regional levels, are uniformly developed in the form of national programs. Consequently, local culture and knowledge are not adequately reflected in the framework and approaches that the provincial and regional governments bring to the implementation of programs for street children. This severely reduces the value and impact of the programs.Drawing from an extensive case study on the intervention programs for street children in Yogyakarta Province, this study explores the major problems surrounding the national intervention programs for street children in Indonesia. It focuses on how national policy and programs are implemented at the provincial and regional levels. For this purpose, this study employed a qualitative approach and used a twofold research methodology, a combination of analyzing the pertinent documentation relating to policy and programs for street children along with serial interviews conducted with key informants from government offices and non-governmental institutions (NGOs).